Demographic characteristics, patterns and outcome of poisoning in emergency department - Pradhananga, Sneha; Shrestha, Trishna; Batajoo, Kabita Hada; Kumar, Alok; Pradhan, Pratisha (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Poisoning is one of the common medical emergencies presenting in the emergency department. It is emerging as a leading cause for suicidal purpose in recent years. This study aims to analyze the characteristics of poisoning based on age, gender, marital status, occupation, poisoning substance, intention, reason for taking poison and its outcome. Method: This is a descriptive prospective cross sectional study conducted at emergency department of KIST Medical College and Teaching Hospital from 20th June 2020 to 19th June 2021. A total of 128 patients who presented with history of oral ingestion of poison were included in this study. Informed consent was taken and preset proforma was filled. Data was then entered in MS Excel and analyzed using STATA 14. Result: The majority of poisoning patients belonged to age group 21-30 years 50 (39.06%), female 75 (58.59%), married 75 (58.59%) and housewife by occupation 35 (27.34%). Common poisoning substance found were organophosphorous 44 (34.38%) followed by zinc phosphide and mixed drugs 20 (15.63%). 103 (80.47%) patients used poisoning for suicidal intention and common reason for taking poison was found to be domestic quarrel 67 (52.43%). Out of 128 patients 74 (57.81%) were admitted, 52 (40.63%) were discharged on patients request and 2 (1.56%) was referred out due to unavailability of intensive care unit bed. Conclusion: Poisoning was found more in female, young adults, married and housewives. Common poisoning agents found was substances which are easily available at home and local shops. Patients are irrationally using these substances for suicidal purpose.